Digital technologies and museums: augmented reality, learning and audience development - Giuseppe Carci; Alessandro Caforio; Christian Gamper (Firenze University Press, 2019)
This study aims to establish whether new digital technologies can provide a more effective museum experience by widening the access for a greater number of visitors and triggering specific learning processes, also through a deeper engagement. To this end, a review of some significant nationally and internationally researches on the effectiveness of digital tools for museums is provided. They describe the technologies with the greatest impact in terms of audience development and knowledge dissemination. This extensive review shows evidences and findings about the possibility given by new technologies and digital and immersive environments (3D models and printing, virtual and augmented reality) to enhance the user experience in museum context. Furthermore, digital and immersive environments offer new, and so far under-explored, ways of learning, as they are able to transfer knowledge triggering the emotional involvement of the audience. Digital technologies need to be integrated into a strategic design aiming to define innovation plans, digital projects management approaches and specific guidelines for creating an effective storytelling.   Tecnologie digitali nei musei: realtà aumentata, apprendimento e audience development L'obiettivo del presente studio è quello di stabilire se le nuove tecnologie possano rendere più efficace l'esperienza museale, favorendo una maggiore fruizione dei visitatori e specifici processi di apprendimento, anche attraverso un più ampio coinvolgimento. A tal fine viene presentata una rassegna di alcune significative ricerche ed esperienze, a livello nazionale e internazionale, sull'efficacia degli strumenti digitali per i musei, descrivendo le tecnologie di maggiore impatto in termini di audience development e diffusione della conoscenza. Dalla ricognizione effettuata emergono stabili riscontri sul fatto che sia possibile rendere molto più efficace l'esperienza museale attraverso le nuove tecnologie e che gli ambienti digitali e immersivi (modelli e stampa 3D, realtà virtuale e aumentata) offrono nuove e poco esplorate modalità di apprendimento, in quanto capaci di trasmettere i contenuti aumentando il coinvolgimento emotivo dei visitatori. Le tecnologie necessitano di essere integrate in una pianificazione strategica che punti a definire un piano di innovazione e pianificazione di progetti digitali e specifiche linee guida nell'impiego per creare uno storytelling efficace.